Plasma Temperature Determination of Hydrogen Containing High-Frequency Electrodeless Lamps by Intensity Distribution Measurements of Hydrogen Molecular Band. (16th November 2009) - Gavare, Zanda; Revalde, Gita; Skudra, Atis
Abstract : The goal of the present work was the investigation of the possibility to use intensity distribution of the Q-branch lines of the hydrogen Fulcher-α diagonal band (d 3 Π u − → a 3 ∑ g + electronic transition; Q-branch withv = v ′ = 2 ) to determine the temperature of hydrogen containing high-frequency electrodeless lamps (HFEDLs). The values of the rotational temperatures have been obtained from the relative intensity distributions for hydrogen-helium and hydrogen-argon HFEDLs depending on the applied current. The results have been compared with the method of temperature derivation from Doppler profiles of He 667.8 nm and Ar 772.4 nm lines. The results of both methods are in good agreement, showing that the method of gas temperature determination from the intensity distribution in the hydrogen Fulcher-α (2-2)Q band can be used for the hydrogen containing HFEDLs. It was observed that the admixture of 10% hydrogen in the argon HFEDLs significantly reduces the gas temperature.